Discourse: The Basic Communication Theories and Models - Esther, Ogundimu Oreoluwa (Budapest International Research and Critics in Linguistics and Education (BirLE) Journal, 2026)
Communication is a fundamental process through which individuals share ideas, negotiate meaning, and influence social realities. Over time, scholars have developed various communication models and theories to explain how messages are produced, transmitted, interpreted, and sometimes misunderstood. This paper examines some of the foundational communication models and theories that have shaped the field of communication studies, including the Shannon-Weaver Model, Lasswell’s Model, Berlo’s SMCR Model, and Schramm’s Interactive Model, as well as key theories such as Agenda-Setting, Uses and Gratifications, Cultivation Theory, and the Two-Step Flow of Communication. The discussion highlights the core assumptions, strengths, and limitations of these frameworks while connecting them to practical communication situations. Particular attention is given to the Nigerian communication environment, where diverse languages, cultural traditions, and evolving media systems influence how messages circulate and are interpreted. Based on the secondary data, the paper establishes that while many communication models originated in Western contexts, their application in developing societies reveals additional cultural and structural complexities. Thus, integrating theoretical explanations with local examples, the paper underscores the continuing relevance of communication theories in understanding modern media practices, public discourse, and social mobilization in Nigeria. The paper, therefore, argues that communication theories remain highly relevant in understanding contemporary media practices, public discourse, and social mobilization in Nigeria. However, these theories must be continuously adapted to reflect the realities of developing societies, especially in an era where digital media and social networking platforms are transforming how communication occurs.